BIOLOGICAL CONTROL OF STRIGA USING FUSARIUM OXYSPORUM - Suh, C.; Akongnwi, C. N.; Nzioki, H.; Gonne, S.; Fankou, M.; Gizachew, Z.; Abebaw, Y.; Chatue, G.; Danbe, N.; Zaiya, A.; Lueth, P.; Sands, C. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study focuses on a low-cost biological control technology using Fusarium oxysporum to enhance smallholder farmers' livelihoods and explores developing fungicide-resistant variants of Fusarium oxysporum (FOXY 6A) for seed treatment, addressing the challenge of applying biological agents on fungicide-coated seeds. Fusarium strains were isolated from infected Striga plants, with three promising isolates identified through PCR. The experiments were conducted at IRAD Maroua, Cameroon. The pot experiment used a controlled study with a factorial design. It tested the effect of four Fusarium oxysporum strains on Striga control with two host (maize and sorghum). For each host, pots had a combination of Fusarium strain and conidial density, plus negative controls without Fusarium. Replication was done by using multiple pots per treatment group. For the fungicide resistant mutant tests, we had three treatments per fungicide. Pot trials demonstrated that applying four fungal strains at a concentration of 3X104 spores/mL significantly reduced Striga emergence in maize and sorghum compared to untreated controls. This reduction is attributed to toxins produced by Fusarium oxysporum, which inhibit parasite seed germination. The study found a positive correlation between Striga emergence and crop yield, indicating that higher Striga populations correspond to lower yields. Fungicide resistance tests on FOXY 6A indicated wider inhibition zones for Thiram and smaller zones for Captan, suggesting potential for developing fungicide-resistant biocontrol strains, although further validation is needed.